HADIS TENTANG LARANGAN PUASA WISHAL (SEBUAH KAJIAN KRITIK SANAD DAN MATAN DALAM KITAB SUNAN ABU DAWUD) - Munandar Munandar (UIN Sumatera Utara Medan, 2019)
Hadith about fasting Wisal is sanad hadith narrated by Imam Abu Dawud through Abdullah bin Maslamah to the Prophet. All shows in terms of interconnectedness sanad as teachers and students as well when viewed in terms of year of birth and year of death they allow to meet. Moreover, critics of hadith many priests ta'dil is appropriate from the point to tsiqqah, justice and the nature of their dhabit.”